Sulfur Mineralization: A Key Process for Diagnosing Its Deficiency in Wheat - Carciocchi, Walter Daniel; Mateos, Julian; Divito, Guillermo; Mateos Inchauspe, Facundo; Sainz Rozas, Hernan Rene (Soil Science Society of America, 2021)
Core Ideas: A simplified balance was used to calculate apparent S mineralization in wheat. Apparent S mineralization predicted relative wheat grain yield. Sulfate‐S before sowing combined with particulate organic C diagnosed S status. Sulfur mineralization in soil should be considered in diagnostic methods based on soil analysis. Consideration of S mineralization could aid the development of S diagnostic methods in wheat (Triticum aestivum L.) but this process has not been investigated under field conditions. The objectives of this study were to evaluate: (i) the use of a simplified S balance to quantify apparent S mineralization (Smin‐app) during the wheat growing cycle, (ii) the relationship between Smin‐app and S mineralization indicators [N mineralized in anaerobic incubation (Nan) and total and particulate organic C (TOC and POC)], and (iii) the reliability of the proposed S mineralization indicators (Nan, TOC, and POC) for diagnosing S availability alone or combined with SO42−–S content at sowing (Sini). Fourteen field experiments were conducted to evaluate grain yield in response to S fertilization. Soil samples were taken before sowing and Sini, Nan, TOC, and POC were determined. Additionally, Smin‐app was calculated in 7 out of 14 experiments through a simplified S balance. The main outcomes were: (i) Smin‐app allowed us to compare S mineralization capacity among soils and was closely related to relative wheat grain yield (R2 = 0.92), (ii) Smin‐app was related to Sini, Nan, TOC, and POC, (iii) POC was the S mineralization indicator that had the best performance for diagnosing S deficiency and its use in combination with Sini allowed for satisfactory diagnosis of S status in wheat via the equation: relative grain yield = 81.5 + (0.19 × Sini) + (1.56 × POC) (Ra2 = 0.66). Sulfur mineralization proved to be an important process for wheat S nutrition.